Direct dehydrogenation of propane over Pd nanoparticles encapsulated within IPC zeolites with tunable pore sizes. (December 2022) - Sajad, Mehran; Zhang, Yuyan; Kubů, Martin; Mazur, Michal; Bulanek, Roman; Čejka, Jiří
Highlights: Pd NPs encapsulated within IPC-2 and IPC-4 zeolites by the ADOR process was prepared. Channel size and zeolite structure play critical role in propane dehydrogenation. Encapsulated Pd NPs show better catalytic performance compared to impregnated Pd NPs. Confining Pd NPs within zeolite prevents undesired sintering. Abstract: Propane dehydrogenation (PDH) yields propene, a valuable feedstock in increasing global demand. Yet, despite recent advances in supported metal nanoparticles (NPs) for such catalytic applications, preventing nanoparticle agglomeration remains a challenge. In this study, we prepared well-dispersed Pd nanoparticles and encapsulated them within IPC-2 and IPC-4 zeolites using the Assembly, Disassembly, Organization, and Reassembly (ADOR) process based on the 3D-2D-3D transformation. By structural and textural analysis, we confirmed the synthesis of two 'ADORable' zeolites incorporated with Pd nanoparticles, namely Pd@IPC-2 and Pd@IPC-4. In the direct dehydrogenation of propane, Pd NPs encapsulated within IPC-2 and IPC-4 zeolites outperformed their impregnated counterparts (Pd/IPC-2 and Pd/IPC-4), with Pd@IPC-2 showing a higher catalytic activity than Pd@IPC-4. Accordingly, in addition to the number of surface Pd atoms, the size of the zeolite channels and the structure of the framework strongly affect the catalytic activity of encapsulated Pd. Moreover, confining Pd NPs inside zeolite channels prevented their sintering and agglomeration during the reaction as Pd NPs in impregnated catalysts expanded during the reaction. However, the structure of the zeolite encapsulated with Pd catalysts partly collapsed due to the harsh conditions of the dehydrogenation reaction, hindering access to Pd NPs, as observed in IR spectra. Therefore, palladium NPs are stable within zeolites and do not sinter, but their catalytic activity gradually decreases with the formation of carbon deposits. Although these deposites are removable by calcination, reactivation does not completely restore the original activity due to framework disruption and limited access to the active species. Graphical abstract: Image, graphical abstract